Surface Roughening of Poly (methyl-methacrylate) Membranes by SF6-Glow-Discharge Plasma Etching - Mohamad A.K.Ahmed; Yaseen H. Mahmood; Sameen F.Mohammed (Tikrit Journal of Pure Science, 2023)
The (100 μm) thick of high density Polymethylmethacrylate PMMA membranes were prepared by solution cast method and treated by (42 W), low pressure, DC-discharge, SF6-Plasma for different exposure time: 10,30,60 and 80 min. The observed changes in membranes surface properties have been characterized by Scanning Electron Microscopy(SEM).The optical properties for plasma treated membranes has been characterized by UV-Visible Spectroscopy. The chemical structure changes have been characterized by Fourier Transformation Infrared Spectroscopy (FTIR).The (SEM) results indicates to significant changes in surface morphology of the polymer membranes after plasma treatment. The UV-Visible spectroscopy results shows clearly reduction of light transmission due to plasma treatment, also the (FTIR) results shows the changes in molecular bonds for polymer chains in surface structure of polymer membranes.